FACTORS INFLUENCING THE MADRASAH WORKING GROUP PROGRAM IN UTILIZING INFORMATION TECHNOLOGY TO SUPPORT GREAT MADRASAS - Megawati, Megawati; Annur, Saipul; Berlian, Zainal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study was to analyze how the Implementation of the Madrasah Working Group Program in Utilizing Information Technology to Support Great Madrasas, Dignified Madrasas at Prabumulih State Aliyah 1 Madrasah. This research is qualitative research. In data collection, researchers used several collection techniques, namely: (1) in-depth interviews, (2) observation, (3) documentation study. The data analysis technique uses the analytical method using the Miles and Huberman Model which consists of three stages, namely: data reduction, data display, and drawing conclusions or verification. The results in this study are the factors that influence the implementation of the Madrasah Working Group Program in Utilizing Information Technology to Support Great Madrasas, Dignified Madrasas at Prabumulih State Aliyah 1 Madrasah. The supporting factors; First, the availability of supporting infrastructure, second, human resources. Third, there is a supportive policy. Fourth, content and applications help. The inhibiting factors that influence are as follows; First, difficulty understanding the technical language of Information Technology. Second, feeling old age. Third, the number of outside routines. Fourth, the lack of information technology facilities or media. Fifth, Funds are still minimal. Sixth, unequal opportunity to attend training